Thermal Energy Storage and Recovery in Fractured Granite Reservoirs: Numerical Modeling and Efficiency Analysis - Nima Gholizadeh Doonechaly; Théo Halter; Alexis Shakas; Mahmoud Hefny; Maren Brehme; Marian Hertrich; Domenico Giardini (Geosciences)
Although Aquifer Thermal Energy Storage (ATES) systems are widely researched, Fractured Thermal Energy Storage (FTES) systems are comparatively underexplored. This study presents a detailed numerical model of a fractured granitic reservoir at the Bedretto underground laboratory in Switzerland, developed using COMSOL Multiphysics. Energy efficiency was evaluated across different flow rates and well configurations, including single-well and doublet systems, as well as for two different temperatures, namely 60 °C and 120 °C. The doublet configuration at an injection temperature of 60 °C with a flow rate of 2 kg/s demonstrated the highest energy efficiency among the cases studied. Potential applications for the stored heat are discussed, with scenarios including district heating for the nearby village and greenhouse heating. The results show that although FTES is associated with unique challenges, it has significant potential as a reliable thermal energy storage method, particularly in regions without suitable aquifers. It can also be considered as a cost-effective and competitive approach for climate mitigation (assuming the system is solely powered by solar-PV). This study provides insights into the viability and optimization of FTES systems and highlights the role of fracture/fault properties in enhancing energy efficiency.